No shelf required 2 [ use and management of electronic books - Polanka, Sue (American Library Association, 2012)
E-book content, devices, and services have created challenges for libraries as well as opportunities. Because the e-book playing field is constantly changing, any predictions are, at best, tenuous. Librarians must be resilient in order to manage, and not be managed by, e-books and their progenies. With their explosive sales and widespread availability over the past few years, e-books have definitively proven that they are here to stay. In this sequel to her first book of the same title, the author dives even deeper into the world of digital distribution. Contributors from across the e-book world offer their perspectives on what is happening now and what to expect in the coming months and years. Included in this resource are: Guidelines for performing traditional library processes such as cataloging, weeding, archiving, and managing e-book accessibility for patrons with special needs; Explorations of topics such as the e-book digital divide and open-access publishing; Case studies from an array of academic, public, and school libraries, offering firsthand accounts of what works, what doesn't, and why; Discussions of the emerging model of the electronic-only library and the rich possibilities of enhanced e-books